microRNA‐146a and ‐155, upregulated by periodontitis and type 2 diabetes in oral fluids, are predicted to regulate SARS‐CoV‐2 oral receptor genes - Roganović, Jelena R. (Journal of periodontology (1970), 2021)
Background Type 2 diabetes and periodontitis predispose to a higher risk of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. Recent studies show upregulation of innate immuno‐regulatory microRNA‐146a and ‐155 in oral fluids of patients with type 2 diabetes as well as of patients with periodontitis. The aim was to investigate whether upregulation of these microRNAs may relate to patient susceptibility to the infection via modulation of SARS‐CoV‐2 cellular entry factors expression. Methods Due to limited experimental feasibility and health risks in Coronavirus Disease 2019, bioinformatic analyses combining with system biology were used as initial investigation of interaction between microRNA‐146 and ‐155 and genes encoding SARS‐CoV‐2 entry factors. Results SARS‐CoV‐2 cellular entry factors are expressed in salivary glands and masticatory mucosa (tongue) at different expression levels, comparable with those measured in lungs and tonsil. MicroRNA‐146 and ‐155 are widely involved in the regulation of SARS‐CoV‐2 oral cellular entry factors and may enhance expression of ACE2 and modulate genes involved in host immunity. Conclusions Diabetes‐ and periodontitis‐induced increase in microRNA‐146a and ‐155 in oral cavity is predicted to upregulate angiotensin‐converting enzyme 2 expression, essential SARS‐CoV‐2 entry receptors, and modulate host antiviral response. As it could suggest increased infectivity of diabetes and periodontitis patients, additional protective measures for periodontists are recommended.